2004
DOI: 10.1017/s0263574704000220
|View full text |Cite
|
Sign up to set email alerts
|

Base invariance of the manipulability index

Abstract: The manipulability index suggested by Yoshikava is an important tool for the design of mechanisms and their control. It represents a quantitative measure of the functionality and the ability for realizing some tasks or groups of tasks. This index is some kind of performance measure and should be taken into consideration in the design phase of a mechanism and also in the design of control algorithms.In this paper two important properties of the manipulability index are investigated. The first part of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Further, derivatives can be calculated analytically. As outlined by Staffetti et al [37], it is not a true metric for distance to a singularity but nonetheless serves as a relative comparison of manipulability qualities between joint configurations [38].…”
Section: Manipulability Measurementioning
confidence: 99%
“…Further, derivatives can be calculated analytically. As outlined by Staffetti et al [37], it is not a true metric for distance to a singularity but nonetheless serves as a relative comparison of manipulability qualities between joint configurations [38].…”
Section: Manipulability Measurementioning
confidence: 99%
“…In [64] the authors have showed that the manipulability index is base invariant, that is, it is independent of the manipulator's first DoF and depends solely on the relative positioning of the links and geometry of the manipulator structure. It is also independent of the location of the operation point ( [13], [64]), where the operation point is defined as the point on the end-effector up which the Jacobian is based [13].…”
Section: Manipulability Indexmentioning
confidence: 99%
“…It is also independent of the location of the operation point ( [13], [64]), where the operation point is defined as the point on the end-effector up which the Jacobian is based [13]. This is another drawback of the manipubility index as it fails to distinguish between a long end-effector and a short one.…”
Section: Manipulability Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Jacobian's determinant is h 1 invariant [3] the uniqueness domains depend only on h 2 ; h 3 . In manipulators with low degrees of freedom, detðJÞ ¼ 0 is easily solved, however, for 6 DoF the solution is much more complicated.…”
Section: The Configuration Subspaces Determinationmentioning
confidence: 99%